Sintesis Nanopartikel Nd-CeO2 Menggunakan Metode Simple Heating untuk Aplikasi Solid Oxide Fuel (SOFCs) - Sriyanti, Ida; Abdullah, Mikrajuddin (Jurnal Natur Indonesia, 2009)
Nd-CeO2 nanoparticles have been synthesized with a simple heating method. The microstructure and morphologyof material were characterized by a Scanning Electron Microscopy (SEM), and the conductivity of the material wasmeasured by an AC Impedance Spectroscopy. At room temperature we obtain a sample prepared at 9% at/at. Ndhave the highest conductivity of 1.47 x 10-4. Scm-1. This conductivity surpass the value reported by Anefleous for Nd-CeO2 (NDC) material prepared by different method. Sample has been 49 nm crystals size obtained from FWHM .Thisresult proves that a simple heating method is the promising for synthesizing electrolyte materials for SOFCapplication.